Managing Family-Related Conflicts in Family Businesses: A Review and Research Agenda. (March 2020) - Qiu, Hong; Freel, Mark
This review examines how family businesses manage family-related conflicts that occur at three interfaces: family-business, family-ownership, and family-business-ownership. We find that work-family conflicts, conflicts of interest, and relationship conflicts are prevalent family-related conflicts. Four conflict management strategies are frequently used to deal with these conflicts: vacillation, domination, separation, and third-party intervention. The popularity of these strategies is influenced by some unique characteristics of family businesses, such as high emotional attachment among family members. By integrating insights from the broader conflict research, paradox and dialectic studies, we develop a research agenda targeted at better connecting family-related conflicts to conflict management strategies.